Structural design of buildings : elemental design - Fu, Feng; Richardson, David (Structural design of buildings, 2024)
Structural Design of Buildings: Elemental Design is the essential reference for all structural engineers involved in the design of buildings and other structures. The book forms part of the Structural Design of Buildings series and focuses on the introduction of building elements and materials. It also introduces retrofitting and materials for thermal upgrade of existing buildings. Broken down into the key areas for understanding and undertaking structural design, and with a fully international approach, this book features coverage of: concrete; steel; timber; masonry; aluminium; glass; thermal upgrading and life cycle impacts. The book provides a comprehensive and practical guide to the design of buildings from a structural perspective. It is a timely and essential read for consultants, designers, technicians and contractors tasked with a holistic approach to structural design.